Cruise ship blues : the underside of the cruise ship industry - Klein, Ross A. (New Society Publishers, 2002)
Cruising is one of the fastest growing industries in the world. Attracting over 12 million passengers a year, cruise ships can now carry over 5,000 people on board. Not surprisingly, this growth is causing huge problems -- problems the industry would rather not acknowledge, and the potential cruiser would have a hard time discovering. Book jacket.